What really matters : living a moral life amidst uncertainty and danger - Kleinman, Arthur (OUP E-Books., 2006)
Tells the stories of a handful of men and women, some of whom have lived through some of the most fundamental transitions of the turbulent twentieth century. Each is caught up in existential moral experiences that define what it means to be human, and their stories reveal just how malleable moral life is.